Listening is learning : conversations between 20th and 21st century teachers - Thoms, Frank, 1938- (Rowman & Littlefield, 2019)
"Listening is Learning invites young teachers to seek the knowledge and advice of former teachers, retired educators, respected veterans, and fellow newcomers. It encourages them to step away from their isolated classrooms and search for best ideas, methods, materials, insights--and moments of success, epiphanies, struggles, methodologies"--